Taking the immersive dynamic visual expression of "Van Gogh Alive" as an example, explore the digital expression of the city brand image - Zhao, Zhujianghe; Zainal Abidin, Sazrinee; Shaari, Nazlina; liu, Meng; Li, ShiHao (Human Resources Management Academic Research Society (HRMARS), 2024)
The article describes the exploration and thinking between the large-scale art exhibition - Van Gogh Dynamic visual digital exhibition and the digital image of the city brand. In 2023, the 170th anniversary of Van Gogh's birth, the multi-screen immersive digital light exhibition "Van Gogh Alive" Special commemorative edition of the World's 90th City will be opened to the public at the Shanghai World Expo Museum. More than 1,000 square meters of space will be used to show the short and crazy life of Van Gogh with digital images, and the immersive exhibition will bring unlimited viewing experience to the audience. These dreamlike dynamic visuals perfectly showcase themed reproductions of Vincent Van Gogh's most famous artistic creations, immersing visitors in an artistic wonderland of projections, images, music and scenes. At the same time, these images and audio and video are spread throughout the exhibition venue. How to think about these exhibitions and explore the impact of panoramic holographic ultra-high-definition representations on visual art. This paper takes digital van Gogh art as the central case, adopts the case study method, and mainly discusses whether the new immersive exhibition mode with traditional culture as the theme can be applied to the promotion of urban brand image. At the same time, it discusses how to use digital immersive expression techniques and combine local cultural elements to make the audience feel immersive and enhance the visual image of the city brand. Through the case of Van Gogh's immersive experience, the audience can feel a different artistic and cultural atmosphere. Combined with the digital light and shadow exhibition of specific large-scale public buildings and landmark buildings, the unique digital memory of the city is reproduced and the charm of the city is enhanced.